(untitled) - Douthwaite, Richard (Totnes, UK, 1999)
The book introduces much needed clarity in the domain of money. The answers of 6 questions used to describe reader through different money systems, a process which facilitates comparisons of the nature, advantages and disadvantages of each money system that the author describes.
Keywords: Money,Money,Money,Money,Tiền,Tiền,Tiền,Tiền; Origin,Social aspects,Political aspects,Economic aspects,Khía cạnh kinh tế,Khía cạnh xã hội,Khía cạnh chính trị,Nguồn gốc